Impact of producer services agglomeration on carbon emission efficiency: An analysis based on the data of enterprises in 108 cities of the Yangtze River Economic Belt - JI Tianzheng, DENG Hongbing, ZHANG Tianling (Ziyuan Kexue, 2023)
[Objective] The purpose of this research is to measure the micro-enterprise agglomeration of producer services, analyze its impact direction and specific degree on carbon emission efficiency, and provide scientific basis for stimulating the positive externality of the environment of producer services agglomeration. [Methods] First, on the basis of agglomeration theory and Schumpeter’s innovation theory, this paper expounds the mechanism of the impact of producer service industries agglomeration on carbon emission efficiency from the aspects of scale effect and technology effect. Secondly, from the perspective of enterprises entry, this research build a composite weighted agglomeration index of producer services that reflects both the “stock” agglomeration of producer services at the macro level and the dynamic “increment” of the entry of micro-enterprises. Finally, the carbon emission efficiency of the Yangtze River Economic Belt is calculated based on the super-efficiency SBM model, and the dynamic spatial Dubin model and panel threshold model are established to empirically test the relationship between the agglomeration of producer services and carbon emission efficiency. [Results] The findings indicate that: (1) The Yangtze River Economic Belt’s carbon emission efficiency has a clear positive spatial spillover effect and a path-dependent feature in time dimension. The carbon emission efficiency of a previous period has a great impact on the carbon emission efficiency of the current period, presenting a “snowball effect”. (2) There is a positive U-shaped relationship between the agglomeration of producer services and carbon emission efficiency. Both the direct effect and the spillover effect of producer services agglomeration on carbon emission efficiency will change from negative to positive. Compared with short-term effects, long-term effects are more significant. (3) The three constraining mechanisms of industrial structure, technological innovation, and marketization all show significant single threshold characteristics. The upgrading of industrial structure and technological innovation significantly enhances the role of producer services agglomeration in promoting carbon emission efficiency, while the improvement of marketization level is conducive to mitigating the adverse impact of producer services agglomeration on carbon emission efficiency. [Conclusion] Finally, based on the analysis results of the positive U-shaped curve, this study put forward recommendations for promoting the low-carbon development of the Yangtze River Economic Belt under the influence and constraint mechanisms.